2021
DOI: 10.3390/cancers13235933
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diet and Lifestyle in Early-Onset Colorectal Cancer: A Systematic Review

Abstract: The incidence of early-onset colorectal cancer, defined as colorectal cancer occurring in young adults under the age of 50, is increasing globally. Knowledge of the etiological factors in young adults is far from complete. Questionable eoCRCs’ exogenous factors are represented by processed meat, sugary drinks, alcohol, Western dietary pattern, overweight and obesity, physical inactivity, and smoking, though with heterogeneous results. Therefore, we performed a systematic review to summarize the current evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 223 publications
(385 reference statements)
2
34
0
Order By: Relevance
“…Excessive alcohol consumption is one of well-established risk factors for CRC 6 , 7 , 8 , 9 and has also been suggested to increase EOCRC risk. 10 , 11 , 12 The causality underlying these observed associations has also been studied previously in Mendelian randomization studies which support a role of alcohol intake in CRC carcinogenesis. 13 , 14 Several studies have examined interactions of CRC-related single nucleotide polymorphisms (SNPs) identified in genome-wide association studies (GWASs) with environmental risk factors on CRC risk, but evidence of gene-environment interaction has remained limited.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Excessive alcohol consumption is one of well-established risk factors for CRC 6 , 7 , 8 , 9 and has also been suggested to increase EOCRC risk. 10 , 11 , 12 The causality underlying these observed associations has also been studied previously in Mendelian randomization studies which support a role of alcohol intake in CRC carcinogenesis. 13 , 14 Several studies have examined interactions of CRC-related single nucleotide polymorphisms (SNPs) identified in genome-wide association studies (GWASs) with environmental risk factors on CRC risk, but evidence of gene-environment interaction has remained limited.…”
Section: Introductionsupporting
confidence: 60%
“…Three recently published systematic reviews comprehensively summarized the evidence on non-genetic risk factors for EOCRC, and suggested alcoholic drinking as a potential risk factor for EOCRC, while only a few studies included in these reviews compared risk factors between early and late-onset CRC in multivariable models. 10 , 11 , 12 Although Syed et al. found a strong association of alcohol consumption with EOCRC, this association was not stronger than the association with LOCRC.…”
Section: Discussionmentioning
confidence: 91%
“…There is a growing body of evidence to suggest that being obese, together with smoking, 31 is linked to early onset CRC, at least partly because of the metabolic syndrome 32 . Several recent systematic review, 33 and meta‐analyses, 34 summarised the evidence and showed that in most large epidemiological studies or meta‐analyses, being obese was associated with early onset CRC, with an estimated RR 1.54 (1.01–2.35) 34 . Some studies reported inconclusive or opposite results, 35,36 and authors suggested that this finding could be explained by the pre‐diagnosis loss of weight in patient with CRC, 116 and the negativity of other studies maybe due to the small sample size 117 .…”
Section: Obesity and Colorectal Cancermentioning
confidence: 99%
“…Emerging evidence suggests that diet is linked to CRC prevention, carcinogenesis, and survival, but the underlying mechanisms still need more investigation [ 9 10 11 ]. Environmental factors, such as diet, are considered to account for the incidence of CRC in some patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%